2007
DOI: 10.1111/j.1600-0501.2007.01342.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of matrix bound parathyroid hormone on bone regeneration

Abstract: It is concluded that an RGD-modified PEG hydrogel containing PTH(1-34) is an effective matrix system to obtain bone regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
98
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(105 citation statements)
references
References 29 publications
6
98
1
Order By: Relevance
“…The histological changes and possible effects of intermittent PTH (1-34) treatment during the early and late phase of periodontal repair were investigated in a rat model of tooth root resorption, in which data indicated a role for PDL cells as potent regulators of periodontal repair by modifying the local microenvironment and point to the anabolic potential of an intermittent PTH administration to support these reparative processes [243]. In 2007, Jung et al [244,245] developed an arginine-glycineaspartic acid (RGD) modified polyethylene glycol (PEG)-based matrix which contained covalently bound peptides of PTH(1-34) to promote bone regeneration around dental implants. In their studies, they found this technique enhanced bone regeneration in a similar magnitude to autogenous bone grafting in both rabbit and foxhound models.…”
Section: Parathyroid Hormonementioning
confidence: 99%
“…The histological changes and possible effects of intermittent PTH (1-34) treatment during the early and late phase of periodontal repair were investigated in a rat model of tooth root resorption, in which data indicated a role for PDL cells as potent regulators of periodontal repair by modifying the local microenvironment and point to the anabolic potential of an intermittent PTH administration to support these reparative processes [243]. In 2007, Jung et al [244,245] developed an arginine-glycineaspartic acid (RGD) modified polyethylene glycol (PEG)-based matrix which contained covalently bound peptides of PTH(1-34) to promote bone regeneration around dental implants. In their studies, they found this technique enhanced bone regeneration in a similar magnitude to autogenous bone grafting in both rabbit and foxhound models.…”
Section: Parathyroid Hormonementioning
confidence: 99%
“…Several local delivery systems have been de veloped already and they have been tested in preclinical animal models, with varying rates of success. In foxhounds, an arginine-glycine-aspartic acid modified polyethylene glycol-based matrix which contained covalently bound peptides of PTH, resulted in significantly more new bone formation but not more bone-to-implant contact after 4 and 12 weeks [37]. In contrast, a systemic PTH administration in a rat model was found to stimulate local bone formation, whereas a local delivery of PTH by using β-tricalcium phosphate did not [38].…”
Section: Future Prospectsmentioning
confidence: 87%
“…Similarly, another group found that PTH protects against periodontitis-associated bone loss (87). Recently, Jung et al (88,89) developed an arginine-glycine-aspartic acid (RGD) modified polyethylene glycol-based matrix (PEG) containing covalently bound peptides of the parathyroid hormone (PTH(1-34)) to promote bone regeneration around dental implants. In their studies, they found this technique enhanced bone regeneration in a similar magnitude as autogenous bone grafting in both rabbit and foxhound models.…”
Section: Growth Factors/cytokines/host Modulating Agentsmentioning
confidence: 98%